The relationship of smoking habits to sleep quality and the risk of hypertension in adolescents in Banjar Adat Pande, Bangli district - Paramurthi, I.A. Pascha; I Gusti Ayu Sri Wahyuni Novianti; Ida Ayu Ratih Wulansari Manuaba; Luh Dian Raika Pramesti (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Adolescence is a period of transition and search for identity, which makes adolescents often follow trends that affect society and the environment. One of the adolescent behaviors caused by environmental exposure is smoking. Repeated smoking behavior will become a habit that can affect sleep quality and the risk of hypertension. This study aimed to determine the relationship between smoking habits and sleep quality with the risk of hypertension in adolescents. Methods: This study used a cross-sectional study design. The sample is determined by purposive sampling. The number of study participants was 52 adolescents. Smoking habits were measured using the Brinkman Index questionnaire, a Sphygmomanometer to measure blood pressure, and the Pittsburgh Quality Index Questionnaire (PSQI) to measure adolescent sleep quality. Computer software analyzed data using a chi-square test to determine the relationship between smoking habits to sleep quality and the risk of hypertension in adolescents. Results: The chi-square test of smoking habits and adolescent sleep quality was shown with a p-value of 0.008. The chi-square test results of smoking habits with risk of hypertension in adolescents were indicated by a p-value of <0.001. Conclusion: There was a significant positive relationship between smoking habits to sleep quality and the risk of hypertension in adolescents.